Developing statistical indicators of the integration of the euro area banking system - Michele Manna (European Central Bank (ECB), 2004)
This paper discusses a wide range of indicators of the degree of integration of the euro area banking system. It is concerned with volume data, a less developed field of research compared with studies on prices/rates. We first set out a methodological framework, a mixture of elementary and more sophisticated statistics which can also be used in other contexts and datasets. We then apply this framework to unconsolidated balance sheet data of banks, aggregated at the national level. The paper offers three main empirical conclusions. First, within the euro area the gap between the cross-border banking activity in wholesale and retail markets is widening. Second, at the same time, with the exception of the home bias, even in retail markets there is increasing neutrality towards the location of the counterparty. Third, following a moderate decline in the wake of EMU, London is once again gaining market shares.
Keywords: C43; D40; G21; L11; 330; balance sheet; banking system; euro area; integration